Ultra‐fast LC–ESI‐MS/MS method for the simultaneous determination of six highly toxic Aconitum alkaloids from Aconiti kusnezoffii radix in rat plasma and its application to a pharmacokinetic study. Issue 1 (January 2014) - Liu, Jingjing; Li, Qing; Yin, Yidi; Liu, Ran; Xu, Huarong; Bi, Kaishun
<x xml:space="preserve">Abstract</x> A fast, sensitive, and efficient ultra‐fast LC–ESI‐MS/MS method was developed for the simultaneous quantitation of six highly toxic Aconitum alkaloids, that is, aconitine, mesaconitine, hypaconitine, benzoylaconine, benzoylmesaconine, and benzoylhypaconine, in rat plasma after oral administration of crude ethanol extracts from Aconiti kusnezoffii radix by ultrasonic extraction, reflux extraction for 1 h, and reflux extraction for 3 h, respectively. The separation of six Aconitum alkaloids and aminopyrine (internal standard) was performed on an InertSustain® C18 column, and the quantification of the analytes was performed on a 4000Q ultra‐fast LC–MS/MS system with turbo ion spray source in the positive ion and multiple‐reaction monitoring mode. Absolute recoveries ranged within 65.06–85.1% for plasma samples. The intra‐ and interday precision and accuracy of analytes were satisfactory. The methods were validated with sensitivity reaching the lower LOQ for aconitine, mesaconitine, hypaconitine, benzoylaconine, benzoylmesaconine, and benzoylhypaconine, which were 0.025, 0.025, 0.050, 0.025, 0.025, and 0.100 ng/mL, respectively. The method was successfully applied to a pharmacokinetic study of six Aconitum alkaloids in rat plasma after oral administration of crude ethanol extracts from the raw root of Aconitum kusnezoffii Reichb. by three different extraction processes.